Strategies to Improve Financial Technology Product Innovation - et al., Agus Mulyana (International Journal of Advanced Science and Technology, 2019)
This research is the result of a research strategy to improve marketing performance through innovation, which is conducted at fin tech service providers in Indonesia. The purpose of this study is to look at the effects of information technology, technology capability, intellectual capital, marketing capability, social environment, and innovation, as an integrated strategy model in improving marketing performance in fin tech service providers in Indonesia. This research was conducted by distributing questionnaires to 72 fin tech companies in various regions in Indonesia, who are members of the Indonesian fin tech association using simple random sampling technique. To analyze the relationship in this study used Partial Least Square path analysis technique. The findings prove that there is a significant influence of information technology capability, marketing capability, intellectual capital and social environment on innovation.